2003
DOI: 10.1097/00001665-200307000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Airway Management in Patients With Isolated Pierre Robin Sequence During the First Year of Life

Abstract: Managing the airway of patients with Pierre Robin sequence is diagnostically and therapeutically challenging. Like many other pathologies, Pierre Robin sequence is best managed with a multidisciplinary team. Providing a comprehensive evaluation is important to detect patients who may have silent events during activities of early life. Children with airway obstruction should have a complete assessment to anatomically define the site of airway obstruction. Therefore, management options can be targeted to the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 15 publications
0
53
0
3
Order By: Relevance
“…6,62,100 Cole et al 101 suggested a unique classification system for RS based on functional parameters: severity of airway obstruction, breathing, and feeding difficulties. Care and caution must be exercised when interpreting recommendations for the whole group, because morphologic phenotype, airway physiology, and severity of RS vary.…”
Section: Conclusion and Offeringmentioning
confidence: 99%
“…6,62,100 Cole et al 101 suggested a unique classification system for RS based on functional parameters: severity of airway obstruction, breathing, and feeding difficulties. Care and caution must be exercised when interpreting recommendations for the whole group, because morphologic phenotype, airway physiology, and severity of RS vary.…”
Section: Conclusion and Offeringmentioning
confidence: 99%
“…Surgical interventions for significant airway narrowing among neonates with PRS include tongue-lip adhesion [4,5,22], mandibular distraction osteogenesis [4,5,12] and tracheostomy [22]. Tracheostomy immediately relieves the upper airway obstruction and is still considered the ''gold standard'' treatment option.…”
Section: Distraction Osteogenesis and Airway Obstructionmentioning
confidence: 99%
“…Although vast majority of the children born with micrognathia or PRS are either asymptomatic or can be treated with conservative management, some patients may have significant respiratory and/or feeding issues, necessitating more aggressive interventions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations